Gynecologic care utilization in asylum-seeking women in New York City - Kelly Bogaert; Elianna Kaplowitz; Sara Wagner; Rachel Carroll-Bennett; Dinali Fernando; Ben McVane; Sheela Maru (Elsevier, 2022)
Introduction: Over 25,000 individuals are granted asylum status in the United States annually. Gender-based violence (GBV) has historically been supported as a claim for persecution to apply for asylum. In women, GBV is a known risk factor for sexually transmitted infections, poor mental health, and worse perinatal outcomes. Less is known about the links between GBV, asylum seekers, and gynecologic outcomes or care utilization. Reported rates of gynecologic care-seeking are low in asylum-seeking women and women with histories of GBV often experience barriers to care. We hypothesized that asylum-seeking women with a history of GBV at the Libertas Center, a comprehensive center for survivors of torture in New York City, would receive low rates of recommended gynecologic screening and infrequent gynecologic care. Materials and methods: This retrospective cross-sectional study included adult self-identified female patients who had completed intake at the Libertas Center from 2005-2020. In order to examine the relationship between GBV and gynecologic care use, patients were included if they had an electronic medical record (EMR) at Elmhurst Hospital, were female, 18 years of age and older, and had ever experienced GBV in their lifetime. EMRs were reviewed for medical and psychiatric diagnoses as well as routine components of gynecologic care and were linked to intake data from the Libertas Center characterizing patients' torture history. The primary outcome of this study was whether or not patients attended a gynecology visit. Demographic characteristics, medical histories, adequacy of gynecologic care, and gynecologic care-seeking behavior were compared between the gynecologic care group and the no gynecologic care group. Results: A total of 249 female patients were seen at the Libertas Center from December 2005 until January 2020 at the time of data collection. The prevalence of GBV in this population was 48%. Among women who suffered GBV, 81 received medical care at Elmhurst Hospital and 44 (54%) received gynecologic care. Nearly 50% of those patients who sought care at Elmhurst carried a diagnosis of post-traumatic stress disorder or depression. Women who received gynecologic care were significantly more likely than those who did not receive gynecologic care to have had an Emergency Room visit (68% vs. 41%), an obstetric visit (32% vs 3%), and/or have been seen by a social worker (46% vs 24%; all p < 0.05). Women who saw a gynecologist were significantly more likely to have completed four basic gynecologic care measures (Pap smear, gonorrhea/chlamydia screen, pelvic exam, and mammogram if applicable) compared to women who did not (77% vs 8%, p < 0.05). Conclusion: This study characterizes the gynecologic care utilization of female patients within a comprehensive care center for survivors of torture. We found a high lifetime rate of gender-based violence of 48% in this population. Adequate gynecologic care was uncommon among those who experienced GBV. However, gynecologic care was significantly more likely in patients receiving gynecologic specialty care, which frequently occurred after initial interaction with another provider (i.e. Emergency Department providers). These findings highlight the importance of trauma-informed care and establishing pathways to help asylum seeking and refugee women receive adequate gynecologic care. Further research is needed to explore specific barriers to gynecologic care in this population, how programs for asylum-seekers can integrate gynecologic care into existing structures for medical and mental healthcare, and how to increase awareness amongst providers on the prevalence of GBV and the gynecologic needs of these patients.